Allyl isothiocyanate enhances brain neuronal plasticity proteins via inhibition of inflammation proteins - Juturu, Vijaya; Çağlayan, Berrak; Kılıç, Ertuğrul; Dalay, Arman; Tuzcu, Mehmet; Erten, Füsun; Günal, Mehmet Yalçın; Altunay, Serdar; Orhan, Cemal; Şahin, Kazım (Lippincott Williams & Wilkins, 2018)
[Abstract Not Available]
Annual Meeting of the American-College-of-Sports-Medicine (ACSM) -- MAY 29-JUN 02, 2018 -- Minneapolis, MN
WOS: 000456870503166
Keywords: Allyl Isothiocyanate; Enhances; Via Inhibition; Inflammation Proteins